Guía de la excursión al Triásico de la Sierra de Prades. - Anadón Monzón, P.; París, R.; Virgili, Carmen; Colombo, F.; Vía Boada, L.; Villalta, J.F.; Esteban Cerdá, M.; Marzo Carpio, M. (Cuadernos de Geología Ibérica, 1977)
Sin resumen